Analisis efektivitas dan kontribusi pajak bumi dan bangunan terhadap Pendapatan Asli Daerah Kota Bandung - Rudiana, Vinda Nurrezivanka; Fadjar, Achmad (Departement Of Accounting, Indonesian Cooperative Institute, Indonesia, 2023)
The success of a country's national development is largely determined by its ability to improve people's welfare. In Indonesia, taxes play an important role because they are the main source of government and development funding. This study aims to determine the effect of the effectiveness and contribution of land and building taxes on the local revenue of the city of Bandung. This study applies a descriptive and verification research approach. The research population is based on Bandung land and building tax data for 2016–2020 and regional income data. This study uses saturated non-probability sampling to select groups (census). This study took sixty samples. Processing using SPSS 23. The results of this study found that the 2016–2020 Bandung City Land and Building Tax averaged 92.59% efficacy. The level of contribution of land and building tax to the local revenue of the City of Bandung in 2016–2020 is still within the moderate criteria, namely 26.38%.